Effectiveness Application of Local Wisdom Ecological Modules Kasepuhan Cisungsang Community Through Utilization of Ecosystems on Student Learning Outcomes of 10th Class in Senior High School - Aditya Rahman; Nurul Anisa; Bambang Ekanara (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
This study aimed to analyze the implementation of learning module of ecology based on local wisdom of society in Kasepuhan Cisungsang. This research and development study was conducted in small scale involving 30 students on SMAN 1 Petir, Serang, Banten. Simple random sampling was used for sampling methods. Instruments for data collections were using objective test, reflection journal, observation sheet and questionnaire. The effectivity of module was rated based on student learning completeness (grade > 65). The result showed 83% of students have completed in cognitive assessment, 87% of students have completed in psychomotor assessment. Questionnaire for student response showed the average value of 43% in very good category and 57% in good category. It can be concluded that the learning modules effective to facilitate student learning outcomes.